Kampaṉum ulakiyal aṟivum - Cuppiramaṇiyaṉ, Ca. Vē., 1929- (Tamiḻp Patippakam, 1981)
Worldly wisdom of Kampar, as reflected in his Rāmāyaṇam, story of Rama, Hindu deity, illustrated with selections from the Kamparāmāyaṇam.